STRENGTH ANALYSIS OF MOORING LUG ON SINGLE BUOY MOORINGAT ARDJUNA MARINE TERMINAL - RACALY WIHARJA (NIM : 13107016); Dosen Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja Krisnal, YULIUS
The need of crude oil and natural gas hasincreased and affected the transportation system of hydrocarbon. Tanker as one of transportation in delivering hydrocarbon can’t always be laid down at harbor. Therefore it’s needed a facility called single buoy mooring that can moor the tanker at offshore. In this final project the wind, current, and wave force will be analyzed based on DNV RP C205 “Environmental Condition and Environmental Load” method and will be calculated using Microsoft Excel 2007 to assist the calculation. Stress analysis on mooring lug is performed by modeling the mooring platform using software. The result of analysis will be compared with allowable stress and yield strength of material to estimate mooring lug strength due to tanker loading. The case study of this project is single buoy mooring at Ardjuna Marine Terminal that mooring FSO Arco Ardjuna. The result of analysis is mooring lug will safe in minimum condition of FSO draft 6 meter, wind speed 27,13 m/s; wave height 3,15 meter; and current speed 0,91 m/s with safety factor 1,3 due to allowable stress and 1,62 due to yield strength. For FSO draft 24 meter, mooring lug will safe in minimum condition of wind speed 39,35 m/s; wave height 4,5 meter; and current speed 0,92 m/s with safety factor 1,11 due to allowable stress and 1,39 due to yield strength. The bigger environmental condition and lesser FSO draft, the bigger the stress occur on mooring lug.